Evaluation of a single strain starter culture, a selected inoculum enrichment, and natural microflora in the processing of Tonda di Cagliari natural table olives: Impact on chemical, microbiological, sensory and texture quality. Issue 2 (December 2015) - Campus, M.; Sedda, P.; Cauli, E.; Piras, F.; Comunian, R.; Paba, A.; Daga, E.; Schirru, S.; Angioni, A.; Zurru, R.; Bandino, G.
Abstract The processing of natural table olives is still empirical and far to be controlled. Taking natural fermentation (NF) as control, the performances of a single strain LAB starter culture (SSL) and a selected inoculum enrichment (SIE) were compared. The results showed that the SIE was more efficient in controlling spoiling microflora (Enterobacteriaceae spp.) compared to SSL and NF. Indeed, Enterobacteriaceae in SIE samples were not detectable starting from 10 days, while in SSL and NF samples starting from 30 days. Both starters rapidly acidified the brine, lowering the pH to safety levels (<4.0) after 12 days, while NF samples reached pH 4.3 after 45 days, and these values were kept constant up to 150 days. Moreover, both starters showed debittering activity, as stated through sensory analyses and HPLC analysis of phenols. Compared to NF samples, SIE and SSL extracts retained more hydroxytyrosol at the end of the process, and this could partially account for their higher scavenging activity. Texture profile analysis (TPA) showed that olives processed with SIE inoculum were firmer and more elastic, compared to SSL inoculated olives, thus resulting more similar to NF samples.